ANALISIS POLA ASUH ORANG TUA TERHADAP GANGGUAN INTERNALISASI, EKSTERNALISASI DAN ATENSI PADA REMAJA - Wairooy, Nabilah Azzah Putri; irwanto, Irwanto; Yulianti, Erikavitri; Febriyana, Nining (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Data regarding emotional and behavioral disorders experienced by children is increasing every year. If this problem is not resolved properly, it will have a bad impact on the development of the teenager in the future, especially on character maturation. This study aims to analyze the relationship between parenting and adolescent behavior and emotions. This research is in the form of observational analytic with a cross-sectional method. The total sample consisted of 542 students from seven junior high schools in Surabaya which were taken by total sampling. The instruments used were KPAA to assess the type of parenting style and PSC-17 to assess the type of disorder indication. The data were analyzed univariately to determine the demographic distribution of the sample, and the bivariate test used the chi-square test to determine the relationship between parenting patterns and behavioral and emotional disorders in adolescents. The highest parenting is permissive (81.5%), authoritarian (8.7%), democratic (8.5%), inconsistent (1.7%). Meanwhile, for the assessment of adolescent emotions and behavior, it was found that adolescents without indication of disorder (58.3%), internalization disorder (24.2%), externalization (5.7%), attention (1.7%), and more than 1 disorder (10.1%). The results of the chi-square test were p=0.436 (p0.05). There is no significant relationship between parenting patterns on adolescent behavior and emotions